O Riso Ausente: Desenho de Infâncias em Seis Contos de Moreira Campos: Infância, A Catita, Os Meninos, Olhos espantados, estrela Vésper, A Matutina e Cassiano - Silva, Marilde Alves da (2008)
This work aims to analyze how the construction of discourse about infancy occurs in Moreira Campos’ prose, starting from the stories: Infância and A Catita from the book As Vozes do morto (1963); Os meninos and Olhos Espantados from the book O Puxador de terço (1969); Cassiano and Estrela Vésper, A matutina from the book A Grande Mosca no copo de leite (1985), which composed the Corpus of the research. Our hypothesis is that the voice which builds an infancy representaton belongs to the narrator, who assumes the discourses in face of the process of discussive emptying the infant character has to go through. As an organizer and a conductor of the discourses, he translates the view of the adult about the child, considering that the term infancy and cognates in their latin origin mean absence of speech, thus, infancy is always another in relation to that one that names and studies it (LAJOLO, 2006, p.229).